ASSESSING THE INFLUENCE OF DIGITAL PUBLIC INFORMATION SYSTEMS ON TRANSPARENCY AND AUDIT OPINIONS: A STUDY OF JAVA’S LOCAL GOVERNMENTS - Indah Kartika Sandhi; Alfistia Maradidya (STABILITY : Journal of Management and Business, 2025)
Digital transformation in the Information and Documentation Management Officer (PPID) services is an important instrument in promoting transparency and accountability of local governments in Indonesia. PPID faces significant challenges in ensuring transparency of public information, particularly in terms of incomplete or outdated data on their websites, as well as weak audit and evaluation processes. There is a lack of comprehensive studies on the success of digitalizing real-time information updates on PPID websites and its impact on the availability of public data to measure accountability.  This research aims to examine the influence of PPID’s digital transformation and the transparency of the publication of Local Government Financial Statements (LKPD) on the likelihood of obtaining an Unqualified Opinion (WTP) of local governments in Java. Logistic regression analysis was used to test the relationship of each variable with the audit opinion. This research conducts cross-sectional design. The results show that digital transformation does not have a significant influence on the audit opinion, but there is a positive and significant relationship between digital transformation and publication transparency. It inferred that having information on PPID website alone is not enough to improve the quality of financial statements (LKPD) to receive an Unqualified Opinion. However, based on the mediation analysis, digital transformation increases transparency but does not serve as a bridge to the influence on the audit opinion. These findings confirm digitalization and transparency as a procedural rather than substantive reinforcing agency theory on persistent information asymmetry even when the information is avaliable. Local governments, Supreme Audit Agency (BPK), and Information Commission should prioritize PPID quality and LKPD consistency over mere platform adoption to achieve accountability gains.